Effects of biuret and lasalocid (Bovatec) inclusion into a commercial mineral supplement on growth performance of yearling calves grazing in the Kansas Flint Hills - Pflughoeft, Madison Grace (Kansas State University, 2023)
Research has demonstrated that using biuret has improved performance in grazing cattle. Lasalocid (BovatecTM), an ionophore, has improved the growth performance of grazing cattle and reduced methane production in growing and finishing cattle. The objective of our experiment was to evaluate the effects of biuret inclusion with and without lasalocid in a commercial mineral mix on the growth performance of yearling beef calves grazing in the Kansas Flint Hills. Over a 2-year period, 742 crossbred steers (initial body weight: 297 ± 23.7 kg) previously backgrounded at the Kansas State Beef Stocker Unit were randomly assigned to one of three mineral treatments (control mineral, control mineral with biuret, and control mineral with biuret + lasalocid). Pastures were previously enrolled in a long-term prescribed fire trial. In the experiment, 18 pastures were blocked by prescribed fire treatment and mineral treatments were assigned randomly to pasture with each mineral treatment represented twice within each prescribed fire treatment. Steers were grazed from May to August for 90 days at a targeted stocking density of 280 kg live-weight ˖ ha⁻¹. Mineral feeders were weighed weekly to determine mineral consumption and refilled weekly with the respective mineral treatment at a target consumption of 113.4 g per head daily. In addition, mineral feeders were checked daily to estimate the number of days until an individual mineral feeder was empty (i.e., days-to-empty). Total body weight gains, average daily gains and mineral consumption did not differ (P ≤ 0.15) among mineral treatments. Final body weights were greater (P ≤ 0.03) for biuret and biuret + lasalocid mineral compared with control. Days-to-empty varied between weeks (P ≤ 0.01), with calves consuming mineral at a slower rate at the initiation of the year of the experiment. There also were variations between days-to-empty and mineral treatment (P ≤ 0.02).
Keywords: Grazing; Ionophore; Mineral; Non-protein nitrogen